Thermal Conversion of Coral Waste and its Utilization as Low-Cost Catalyst for Biodiesel Production - Widianingsih, Suci; Yanti , Ika; Kamari, Azlan; Fatimah, Is (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This study investigates the thermal conversion of waste coral and its utilization as a heterogeneous catalyst for biodiesel production from soybean oil. In this work, waste coral is calcined at varied temperatures of 800, 900, and 1000°C, and the effect of the calcination temperature on the physicochemical character of the solid is evaluated through Fourier-transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and basicity measurement. The results show that the higher temperature facilitates the conversion of CaCO3 of the aragonite and calcite phases in raw waste coral into CaO, achieving a complete conversion at the temperature of 1000°C. Thermal conversion influences the increased surface basicity of the solid, which is associated with the higher activity for biodiesel production. Further studies on the obtained CaO as a catalyst demonstrate the catalyst dosage and the methanol-to-oil ratio as significant factors for fatty acid methyl ester production. The highest yield of 98.7% is achieved after a 3 hours reaction with 8 wt.% catalyst dosage and 9:1 methanol-to-oil ratio. The catalyst exhibits stability with an insignificantly decreased yield until the fifth usage cycle. The optimum conditions and reusability features of the calcined waste coral suggest that waste coral is a favorable CaO catalyst source for biodiesel production.